2016
DOI: 10.1002/tox.22298
|View full text |Cite
|
Sign up to set email alerts
|

Benzo[a]pyrene induced p53-mediated cell cycle arrest, DNA repair, and apoptosis pathways in Chinese rare minnow (Gobiocypris rarus)

Abstract: The p53 pathways play an important role in carcinogenesis. In mammals, p53 and p53 target genes have been extensively studied, but little is known about their functions and regulation in fish. In this study, the cDNA fragments of p53 network genes, including p53, p21, mdm2, gadd45α, gadd45β, igfbp-3, and bax, were cloned from Chinese rare minnow (Gobiocypris rarus). These genes displayed high amino acid sequence identities with their zebrafish orthologs. The mRNA levels of p53 network genes and pathological ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…Each sample was run in triplicate. The primers in this study are shown in Table S1 (Yuan et al, 2016). The PCR efficiencies ranged from 93.2% to 103.0% in the present study.…”
Section: Rt-qpcrmentioning
confidence: 64%
“…Each sample was run in triplicate. The primers in this study are shown in Table S1 (Yuan et al, 2016). The PCR efficiencies ranged from 93.2% to 103.0% in the present study.…”
Section: Rt-qpcrmentioning
confidence: 64%
“…They do not provide insights into the underlying molecular mechanisms responsible for toxicity. For that purpose and considering that other studies have reported that PAHs and HPAHs could induce oxidative stress and apoptosis , complementary methods were used in the present study to characterize these effects.…”
Section: Resultsmentioning
confidence: 99%
“…Several signaling pathways have been shown to be activated by the presence of reactive oxygen species, a by-product of cellular activation by BaP [ 111 , 143 , 144 , 145 , 146 , 147 , 148 , 149 ]. The PI3K-Akt signaling pathway is one of the most important pathways involved in the proliferation and survival of cells [ 150 , 151 , 152 ].…”
Section: Discussionmentioning
confidence: 99%